La resignificación de los rituales alrededor de la fiesta en honor a la virgen de las mercedes en la población de Latacunga. - Valencia Tigse, Janneth Alexandra (2018)
The present research work is based on the processes of resignification of the rituals that are carried out in honor of the Virgin of the Virgen de las Mercedes for the conformation of the traditional dancing of the Mama Negra. The objective of this work was to identify resignification processes, as well as changes in reality, from the reactivation of the Cotopaxi volcano in August 2015. In addition, it is focused on the community, directly benefiting devotees and donors from La Merced and El Salto, who can know the different processes of resignification of the traditional celebration; and indirectly to all citizens of Latacunga. This research was designed with a qualitative approach, in which three techniques were used with the devotees and donors of the La Merced and El Salto popular markets: a focus group, semi-structured interviews and life stories. The intention of these techniques is to know the rituals and their changes in the festivity. The results obtained in the investigation evidenced the changes in the rituals of the reactivation of the Cotopaxi volcano, the increase of the faith and devotion, as well as the increase of the participation of donors and donors of the comparsas.